Analysis on marine monitoring and data service of marine internet - Chao DONG; Yankun CHEN (Dianxin kexue)
China has abundant marine resources and provides new ideas for alleviating the shortage of resources.At the same time,natural disasters in the sea caused great economic losses in the coastal areas.Therefore,in the process of marine development and utilization,there is an increasing need for an ocean interconnected information network that can provide real-time marine sampling,environmental monitoring,underwater exploration,and disaster warning applications.Firstly,the characteristics of marine monitoring methods and monitoring data were introduced in detail.Then,taking the oceanography survey of China and the business characteristics of sea-gas CO2exchange flux monitoring as examples,it was found that in the long-term marine monitoring task,there were three issues that needed to be solved urgently,including the needs of the marine monitoring internet business,the needs of shared platforms in the context of marine monitoring big data,and the needs of submarine observation networks.